Low-Calorie Sweeteners and Reproductive Health: Evidence and Debates - Atalay, Ece Çelik; Demirhan, Buket Er; Celep, Adviye Gülçin Sağdıçoğlu (Current Nutrition & Food Science, 2025)
The reduction in sugar consumption has led to increased use of low-calorie artificial sweeteners. This coincides with an increase in infertility rates, suggesting that low-calorie artificial sweeteners may negatively affect reproductive health. Low-calorie sweeteners may affect oxidative stress, glucose regulation, and the microbiota, which are associated with reproductive health. Therefore, a review was conducted to examine the effects of commonly used low-calorie sweeteners on reproductive health through potential biological mechanisms. This review addresses the effects of low-calorie sweeteners in a wide range of areas, such as infertility, pregnancy and neonatal health, and early menarche. Recent studies have indicated potential adverse effects of artificial sweeteners on reproductive health. Research has examined the potential impacts of artificial sweeteners on various parameters, such as hormone levels, sperm quality, sperm motility, ovarian function, and pregnancy outcomes. However, the findings of current studies are inconsistent, and these disparate results may stem from metabolic differences among different types of artificial sweeteners, variations in research methodologies, diversity in sample sizes, and fluctuations in study populations. Therefore, further research is needed to comprehensively understand the effects of artificial sweeteners on reproductive health.
Keywords: pregnancy